Emerging markets instability : do sovereign ratings affect country risk and stock returns? - Kaminsky, Graciela L. 1982- (Policy research working paper, 2001)
Changes in sovereign ratings affect country risk and stock returns. And these changes are transmitted across countries, with neighbor-country effects being more significant